Time from injury to acute surgery for patients with traumatic cervical spinal cord injury in South-East Norway - Aarhus, Mads; Mirzamohammadi, Jalal; Rønning, Pål Andre; Strøm, Mona; Glott, Thomas; Rizvi, Syed Ali Mujtaba; Biernat, Donata; Ølstørn, Håvard; Rydning, Pål Nicolay Fougner; Stenset, Vidar Tveit Vasfaret; Næss, Pål Aksel; Gaarder, Christine; et al. (Frontiers in Neurology, 2024)
Background The recommended treatment for cervical spinal cord injury (cSCI) is surgical decompression and stabilization within 24 h after injury. The aims of the study were to estimate our institutional compliance with this recommendation and identify potential factors associated with surgical delay. Methods Population-based retrospective database study of patients operated for cSCI in 2015–2022 within the South-East Norway Health Region (3.1 million inhabitants). Data extracted were demographics, injury description, management timeline, place of primary triage [local hospital (LH) or neurotrauma center (NTC)]. Main outcome variables were: (1) time from injury to surgery at NTC, (2) time from injury to admission NTC, and (3) time from admission NTC to surgery. Results We found 243 cSCI patients having acute neck surgery. Their median age was 63 years (IQR 47–74 years), 77% were male, 48% were ≥65 years old. Primary triage at an LH occurred in 150/243 (62%). The median time from injury to acute surgery was 27.8 h (IQR 15.4–61.9 h), and 47% had surgery within 24 h. The median time from injury to NTC admission was 5.6 h (IQR 1.9–19.4 h), and 67% of the patients were admitted to the NTC within 12 h. Significant factors associated with increased time from injury to NTC admission were transfer via LH, severe preinjury comorbidities, less severe cSCI, time of injury other than night, absence of multiple injuries. The median time from NTC admission to surgery was 16.7 h (IQR 9.5–31.0 h), and 70% had surgery within 24 h. Significant factors associated with increased time from NTC admission to surgery were increasing age and non-translational injury morphology. Conclusion Less than half of the patients with cSCI were operated on within the recommended 24 h time frame after injury. To increase the fraction of early surgery, we suggest the following: (1) patients with clinical suspicion of cSCI should be transported directly to the NTC from the scene of the accident, (2) MRI should be performed only at the NTC, (3) at the NTC, surgery should commence on the same calendar day as arrival or as the first operation the following day.